Functional Connectivity Patterns and the Role of 5-HTTLPR Polymorphism on Network Architecture in Female Patients With Anorexia Nervosa - Collantoni, Enrico; Meneguzzo, Paolo; Solmi, Marco; Tenconi, Elena; Manara, Renzo; Favaro, Angela (Frontiers in Neuroscience, 2019)
INTRODUCTION Recent neuroimaging studies suggest that Anorexia Nervosa (AN) symptoms emerge from failures in the relationships between spatially distributed networks that support different cognitive, emotional and somatosensory functions. The 5-HTTLPR genotype has been shown to modulate all these abilities in AN, as well as the connectivity patterns between brain regions that support their functioning. This study aims at exploring the presence of any difference in functional connectome properties between AN patients and healthy controls (HC) by means of graph theory tools. The effect of 5-HTTLPR genotype on regional and global network characteristics in AN and HC was also explored. METHODS A sample of 74 subjects (38 HC, 36 AN) underwent a resting state functional magnetic resonance imaging and was genotyped for 5-HTTLPR polymorphism. Comparisons of network properties were made between the AN and HC groups and, within each group, between 5-HTTLPR carriers of low-functioning alleles and carriers of the long-long genotype. RESULTS Patients with AN displayed lower network clustering than HC (p<0.04 at Mann-Whitney’s U Test). Based on both degree and betweenness, a different distribution of network hubs emerged in the two groups. In particular, the anterior part of the anterior cingulate cortex was a hub only in the patient group. A correlation emerged between differences in brain volumes between patients and HC and differences in degree values of basal ganglia, nodes in the insula and those in the parietal cortex. Carriers of the short allele of the 5-HTTLPR polymorphism were characterized by lower small-world properties (p=0.027) and modularity (p=0.031) in the patients group, and a trend towards higher modularity (p=0.033) and small-world values (p=0.123) in the HC group. DISCUSSION Patients with AN showed differences in hubs distribution, providing evidence of the presence of a different functional architectural backbone in this group. Since some correlation emerged between different degree values of nodes and differences in volumes, further longitudinal studies are warranted to better understand the role of malnutrition on brain network architecture. The opposite effects of 5-HTTLPR polymorphism on global network characteristics in the two groups suggests an interaction of the short allele and malnutrition in modulating brain network properties.